Surfactant modification of banana trunk as low-cost adsorbents and their high benzene adsorptive removal performance from aqueous solution - Kong, H. (Royal Society of Chemistry, 2016)
The banana trunk was modified using cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulphate (SDS), poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (Pluronic 123), and 4-(1,1,3,3-tetramethylbutyl)phenyl-polyethylene glycol (Triton X-100) to develop novel low-cost adsorbents for benzene removal from aqueous solution. The surface morphology and functional groups of the synthesized adsorbents were determined by a field emission scanning electron microscope (FESEM) and a Fourier transform infrared (FTIR) spectrophotometer. The Brunauer, Emmett and Teller (BET) analysis and X-ray photoelectron spectroscopy (XPS) were also conducted to study adsorbent characteristics. The benzene adsorptive performance of the synthesized adsorbents was evaluated in a batch adsorption experiment at various experimental conditions. It was found that the highest benzene adsorption capacity (280.890 Ã 10-3 mmol g-1) was obtained for M-TX100-BT. The fundamental adsorption studies revealed that the benzene adsorption process was found to be thermodynamically non-spontaneous and all were fitted well by the Langmuir isotherm model. The adsorption kinetic data obeyed the pseudo-second kinetic model with the film diffusion as the rate-limiting step. The application prospects of the Triton X-100 modified banana trunk adsorbent were demonstrated through the regeneration study which revealed that it can also be repeatedly used for at least up to five-adsorption/desorption cycles and its adsorption capacity was comparable to the literature data of similar adsorbents. Thus, banana trunk agrowaste could be an alternative low-cost adsorbent precursor for the adsorptive benzene removal from an aqueous solution. Â© The Royal Society of Chemistry 2016.